Development of multi-item EOQ when the constraints of investment and storage capacity are active - Ghafour, Karzan Mahdi; Ramli, Razamin; Zabidi, Nerda Zura (2015)
The liability in inventory models decide of “how much or how many” of inventory items to order.The economic order quantity (EOQ) varies from one model to another, depending on assumptions and variables.This paper has developed the EOQ in deterministic inventory model of multi-item when the objective function is subjected to investment and capacity of shortage space constraints.The constraints are assumed to be active if the left hand side does not satisfy the right hand side condition.Thus, Lagrange method is used to find the new multi-item EOQ in each four models with each constraint to achieve the new formula of EOQ.